Rede mafrensina: sociabilidade e diálogo epistolar entre intelectuais piauienses de 1980 a 1995 - Tapety, Audrey Maria Mendes de Freitas (2017)
This thesis intends to show how a network of sociabilities among oeirense/piaui/brazilian intellectuals was constituted between epistolary interlocution, having as main sources the personal documents of Possidônio Nunes Queiroz: letters, chronicles, articles of the Magazine of Instituto Histórico de Oeiras and radio programs scripts. In this work, I approach the relations of friendship built between Men of Letters from oeirense/piaui/brazilian, and from the reasons that led them to the constitution and consolidation of the “network of sociability Mafrensina”, so named because of the nomenclature used by them when refer to the city of Oeiras, where Domingos Afonso Mafrense lived, a “pioneer” of this territory, where most of the intellectuals referred to in the thesis were born. In missives, intellectuals have carved pictures of themselves from their own perception and from the perception of the other. I highlight the symptoms that gravitated in the universe of Piauían literary production in the temporal cut from 1980 to 1995, and how they were constituted as subjects of knowledge. The work reflects the forms of construction of correspondence subjectivity, their experiences and experiences through the faculty of Memory, and how they translated the society in which they lived. In the space of family correspondences exchanged between the main character – Possidônio Nunes Queiroz – and his sons and friends, the themes dealt with spontaneously dealt with the subject's relationship with the feeling of nostalgic, loss, counselling and aging. Possidônio, a man of immeasurable knowledge and a devout attitude towards his native city, possesses a vast historical, literary and musical production. Although he did not compile his knowledge in a single published work, he deserved to have been elected to a chair at the Piauiense Academy of Letters (APL), which probably did not happen because he did not have socioeconomic support